PENGARUH JARAK ANTAR PISAU DAN SUDUT HOPPER TERHADAP KINERJA MESIN PEMARUT KAYU - Rahmatulloh, Dion Eka; Qiram, Ikhwanul; Mukhtar, Anas (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Wood chipper machine is a tool used to crush wood waste into powder (particles). This study aims to determine the effect of the distance between the blades and the hopper angle due to wood chipper machine performance. The distance between the blades was varied by 2 mm and 3 mm. The hopper angle was varied by 45o, 50o, and 55o. Measurement of sengon wood particles is done by using wire-mesh with sizes of 1.19 mm, 0.25 mm, and 0.15 mm. The result of the study show that there is an effect of the distance between the blades and the hopper angle due to wood chipper machine performance.